The Protective Roles of Vitamin E and α-Lipoic Acid Against Nephrotoxicity, Lipid Peroxidation, and Inflammatory Damage Induced by Gold Nanoparticles - Abdelhalim MAK (Dove Medical Press, 2020)
Mohamed Anwar K Abdelhalim, Huda AY Qaid, Yanallah H Al-Mohy, Magdi Mohamed Ghannam Department of Physics and Astronomy, College of Science, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Mohamed Anwar K AbdelhalimBiomedical Physics, Department of Physics and Astronomy, College of Science, King Saud University, P.O. 2455, Riyadh 11451, Saudi ArabiaTel +966509649633Email abdelhalimmak@yahoo.comBackground: Recently, use of nanotechnology in biomedical applications such as drug delivery and diagnostic and therapeutic tools has increased greatly. This study evaluated gold nanoparticle (GNPs)-induced nephrotoxic effects in rats in vivo, and examined protective effects of alpha-lipoic acid (α-Lip) and Vitamin E (Vit E) against nephrotoxicity, lipid peroxidation, and inflammatory kidney damage induced by GNPs.Materials and Methods: Twenty-four male Wistar-Kyoto rats (220– 240 g, 12 weeks old) were dosed with 50 μL of 10 nm GNPs administered intraperitoneally with or without 200 mg/kg/day Vit E or 200 mg/kg/day α-Lip. Serum was prepared for biochemical analyses. Kidney function was evaluated through measurement of creatinine (CR), uric acid (URIC), and blood urea nitrogen (BUN). Oxidative stress and lipid peroxidation were evaluated by measurement of reduced glutathione (GSH) and malondialdehyde (MDA) in kidney tissue homogenates.Results and Conclusions: The results showed a significant rise in serum kidney function biomarkers including urea, URIC, CR, and BUN in GNP-treated rats compared to normal control rats. Furthermore, GNPs led to decreased GSH and elevated MDA levels. Vit E or α-Lip supplementation showed a beneficial effect against nephrotoxicity, lipid peroxidation, and inflammatory kidney damage induced by GNPs. This study suggests that use of natural antioxidants in combination with GNPs may be a useful tool in preventing GNPs toxicity.Keywords: gold nanoparticles, Vitamin E, alpha-lipoic acid, nephrotoxicity, lipid peroxidation, natural antioxidants